A Spacecraft Launch Organizational Reliability Model Based on CSF. (22nd August 2012) - Xuejun, Dong; Yingwu, Chen; Ming, Li; Yingxin, Zhang
Abstract : Organizational reliability, with regard to safety, needs to be assessed for the launch of spacecraft. In this paper, the compensatory and irreplaceable factor is defined while the organizational reliability of a spacecraft launch is researched by studying the decomposition and composition of factors. The factors of space and the characteristics of the organizational reliability of a spacecraft launch are analyzed. The composition method for the states of compensatory and irreplaceable factors is then established, and the overall organizational reliability model of spacecraft launch is constructed. This paper also uses the grey relational analysis technique to analyze and construct a model to assess the organizational maturity of important factors affecting organizational reliability. Finally, a case analysis demonstrates the application of the organizational reliability assessment model of a spacecraft launch, which validates the feasibility and effectiveness of the composition of states of factors. Copyright © 2012 John Wiley & Sons, Ltd.